LA CHARITÉ À L’ÉPREUVE DE LA RÉCONCILIATION DANS LES COMMUNAUTÉS RELIGIEUSES ODJOUKROU (CÔTE D’IVOIRE) - Raymond, Mel Mèlèdje (European Scientific Journal, ESJ, 2014)
Queen of all virtues, charity in the Christian viewpoint of reconciliation demands more love for God and for one’s fellow man. Therefore, the fraternal charity and the “ɔtʃap”, the subsequent forgiveness, as experienced by the Odjoukrou, are limited, though they open onto new prospects of togetherness, well-being and peace. Onward to the Father, Christians are requested to a pressing “Transcendatation” in order to open themselves up to others whenever occasions occur, and also to communicate and spread Christ’s Love around them.